(5x-1)2 =(4)2
=> 5x-1=4
5x=5
x=1
k mk nhé
\(\left(5.x-1\right)^2=4^2\)
\(=>\left(5.x-1\right)=4\)
\(=>5.x=5\)
\(=>x=1\)
5x - 1 = \(\orbr{\begin{cases}4\\-4\end{cases}}\)
với 5x -1 = 4 => x= 1
với 5x-1 = -4 => x= -3/5
\(\left(5.x-1\right)^2=16\)
\(\left(5.x-1\right)^2=\left(+-4\right)^2\)
\(\cdot5.x-1=4\)
\(5.x=4+1=5\)
\(x=5:5=1\)
\(\cdot5.x-1=-4\)
\(5.x=-4+1=-3\)
\(x=-3:5=-0,6\)
\(\left(5x-1\right)^2=16\)
\(\left(5x-1\right)^2=4^2\)
\(5x-1=4\)
\(5x=4+1\)
\(5x=5\)
\(x=1\)
Ta có:16=4^2 nên:
(5.x-1)^2=4^2
=> 5.x-1=4
5.x =4+1
5.x =5
x =5:5
x =1
KB VS MIK NHA.......
(5x-1)2=16
<=>(5x-1)2-16=0
<=>(5x-1-4)(5x-1+4)=0
<=>(5x-5)(5x-3)=0
\(\orbr{\begin{cases}5x-5=0\\5x-3=0\end{cases}}\)
\(\orbr{\begin{cases}x=1\\x=\frac{3}{5}\end{cases}}\)